Effective use of patient-centric health information systems: The influence of patient emotions - Azadeh SAVOLI; Henri BARKI (Systèmes d’information et management, 2022)
The present study examined how patients’ emotional responses to a Portal (i.e., a patient-centric health IT designed to help patients self-manage their chronic condition) influenced their effective use of the Portal. Based on interview data collected from 34 asthma patients, we identified six categories of emotions that the Portal’s usage evoked in patients who participated in the study. While patients who had negative emotions about the Portal tended to always use it ineffectively, the effectiveness with which patients who had positive emotions used the Portal varied according to their differing perceptions of the Portal. In addition, while all positive emotions were associated with high frequencies of Portal use, this usage was not always effective as it was sometimes not aligned with the Portal’s goal of asthma self-management. These findings suggest that designers and implementers need to pay greater attention to the emotional responses that patient-users can have, and to try to minimize the emergence of negative emotions by designing systems that induce in patients a positive experience and self-image, as well as joy while promoting their effective usage of these systems.